Knowledge and conduct on oral health of Elementary School teacher in a municipality of Alagoas (Research, Society and Development, 2021)
The present study aimed to assess the knowledge about oral health of teachers in public elementary schools in a municipality in Alagoas and to identify the behaviors adopted by teachers in face of the most frequent oral problems. For this, a descriptive study was carried out, with a quantitative approach, with 77 professors, through an electronic questionnaire organized in two parts: the first, on sociodemographic aspects and pedagogical practices of oral health, and the second, with specific questions about the basic knowledge of oral health and the behavior that teachers would take in face of the most frequent dental problems. Teachers had a period of two weeks to return the questionnaire. With regard to oral health, it was found that 88.3% of teachers said they knew about caries, 96.1% how to avoid it and 71.4% said they knew how to brush students' teeth. Regarding behavior and attitudes, it was found that 62.3% of teachers did not take students to brush their teeth; 62.3% did not know what to do in the face of an accident that affected the student's mouth and 94.8% would not keep the student in the classroom due to the specific complaint of toothache. From the analyzed data, it is concluded that the knowledge and behavior presented by the teachers were considered unsatisfactory and often superficial, as they started predominantly from daily practice (empirical knowledge) and were not permeated, in most cases, by information enough techniques.